Transformational leadership at Al-Hafza Academy in Jordan and its role in enabling female teachers to manage the crisis and master distance education skills during the Corona pandemic (Covid-19 ) - Al-Shamayleh, Fatima Muhammad Salama (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the reality of transformational performance at Al-Hafza Academy and its role in the parameters of crisis management and mastering distance learning skills during the Corona pandemic (Covid-19). assemblies, three assemblies, three assemblies operating parameters on the transducer transformer (3.86), and at the level of the axes; As follows: First: The role of leadership in the outcrops that lead to increased air circulation. Second: turn. The distance learning skills needed for teachers to meet the challenges posed by the Corona pandemic. With an arithmetic average of (4.32) to a very large degree. And thirdly: The role of transformational leadership for school principals in enabling female teachers to learn distance learning skills in light of the Corona pandemic, with an average of (4.29) to a very large degree. Fourth and penultimate: the axis of health and educational crisis management to confront the challenges posed by the Corona pandemic came to a medium degree with an arithmetic average (3.66). Finally, the reality of using the Al-Hafiz Academy for Transformational Leadership was the reality of using the Al-Hafza Academy for Transformational Leadership (2.62) to a medium degree. The results also showed the weakness of school principals in Jordan’s use of transformational leadership as a method in school management. The most important recommendations of the request were activating transformational leadership and empowering female teachers in conservation schools and all schools in Jordan.